2020
DOI: 10.1177/2050312120954695
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and determinants of drug therapy problems among type 2 diabetes mellitus patients with hypertension in Ethiopia

Abstract: Introduction: Type 2 diabetes mellitus patients with hypertension are at high risk of drug therapy problems since they are subject to receive multiple drug therapies due to comorbidities. Objectives: To determine the magnitude of drug therapy problems and its determinants among Type 2 diabetes mellitus patients with hypertension. Methods: A cross-sectional study was employed among 423 randomly selected participants based on the inclusion criteria. A structured questionnaire and review of patients’ medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 37 publications
4
16
5
1
Order By: Relevance
“…The study by Kefale et al . 26 had 100% patients having both hypertension and diabetes mellitus, whereas our study had only 32.5% having both conditions. The high proportion of ‘dosage too low’ in our setting could be attributed to prescribing an ineffective dose and too infrequent dosing.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The study by Kefale et al . 26 had 100% patients having both hypertension and diabetes mellitus, whereas our study had only 32.5% having both conditions. The high proportion of ‘dosage too low’ in our setting could be attributed to prescribing an ineffective dose and too infrequent dosing.…”
Section: Discussioncontrasting
confidence: 59%
“…The current prevalence of antihypertensive-related DTPs of 61.8% is comparable to other studies in Northwest, Ethiopia (62.4%), Eastern Ethiopia (60.5%), Northern Ethiopia (55.6%) and Indonesia (57%). 7 , 14 , 26 , 34 However, this finding is lower than 71.2% and 80.7% both in Eastern Ethiopia as well as 82% in Southwest Ethiopia. 15 , 19 , 25 In addition, studies conducted in Malaysia showed that 88.8% and 90.5% participants had at least one DTP.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…These results are in contrast with previous studies in which most of the DTPs were ascribed to patients’ non-compliance towards medications. 25 Two points are emerging here, firstly, the lack of a unified insulin regimen, and secondly, underrating the problems related to indication and effectiveness categories hurdle the patients to achieving a desired therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%